The influence of dietary diversity on the nutritional status of children between 6 and 23 months of age in Tanzania - Khamis, Ahmed Gharib (BMC Pediatr, 2019)
BACKGROUND: Undernutrition poses a serious health challenge in developing countries and Tanzania has the highest undernutrition burden of Eastern and Southern Africa. Poor infant and young child feeding practices have been identified as the main causes for undernutrition. As dietary diversity is a major requirement if children are to get all essential nutrients, it can thus be used as one of the core indicators when assessing feeding practices and nutrition of children. Therefore, adequate information on the association between dietary diversity and undernutrition to identify potential strategies for the prevention of undernutrition is critical. Here we examined to what extent dietary diversity is associated with undernutrition among children of 6 to 23 months in Tanzania. METHODS: Using existing data from the Tanzania Demographic and Health Survey of 2015–2016, we carried out secondary data analysis. Stunting, Wasting and Underweight of the surveyed children were calculated from Z-scores of Height-for-age (HAZ), Weight-for-height (WHZ) and Weight-for-age (WAZ) based on 2006 WHO standards. A composite dietary diversity score was created by summing the number of food groups eaten the previous day as reported for each child by the mother ranging from 0 to 7. Then, minimum dietary diversity (MDD) of 4 food groups out of seven was used to assess the diversity of the diet given to children. Bivariate and multivariate logistic regression techniques were used to assess the crude and adjusted odds ratios of stunting, wasting and being underweight. RESULTS: A total of 2960 children were enrolled in this study. The prevalence of stunting was 31%, wasting 6% and underweight 14%. Among all children, 51% were female and 49% male. The majority (74%) of children did not reach the MDD. The most commonly consumed types of foods were grains, roots and tubers (91%), and Vitamin A containing fruits and vegetables (65%). The remaining food groups were reported to be consumed by a much lower proportion of children, including eggs (7%), meat and fish (36%), milk and dairy products (22%), as well as legumes and nuts (35%), and other vegetables (21%). Consumption of a diverse diet was significantly associated with a reduction of stunting, wasting and being underweight in children. The likelihood of being stunted, wasted and underweight was found to decrease as the number of food groups consumed increased. Children who did not receive the MDD had a significantly higher likelihood of being stunted (AOR = 1.37, 95% CI; 1.13–1.65) and underweight (AOR = 1.49, 95% CI; 1.15–1.92), but this was not the case for wasting. Consumption of animal-source foods has been found to be associated with reduced stunting among children. CONCLUSION: Consumption of a diverse diet is associated with a reduction in undernutrition among children of 6 to 23 months in Tanzania. Measures to improve the type of complementary foods in order to meet the energy and nutritional demands of children should be considered in Tanzania.